The effectiveness of a digital behavior contract on children with autism spectrum disorder: a multiple probe single-subject design study. - Ceyhun, Ayşe Tuba; Kaya, Saadet Sevinç (International Journal of Developmental Disabilities, 2026)
Children with Autism Spectrum Disorder (ASD) often display problem behaviors that interfere with instructional engagement and limit learning opportunities. This study examined the effects of a digitally delivered behavior contract designed to support task engagement by teaching children to remain seated during instructional activities. The digital contract integrated visual timers, animated feedback, and immediate reinforcement cues to enhance procedural clarity and motivation. The study was conducted with three children diagnosed with ASD (two boys aged 7–8 and one girl aged 8) in Istanbul, Türkiye, using a multiple-probe single-subject design across participants. Participants were selected through purposive sampling based on diagnosis, behavioral needs, and regular classroom attendance. Results indicated that all participants acquired the target behavior and demonstrated high levels of independent performance, which were maintained during follow-up sessions conducted in the second, fourth, and sixth weeks (Tau-U effect sizes ranged from 0.88 to 0.92, p < 0.01). Generalization probes across different instructors showed consistent performance under limited contextual variations. Parent and teacher social validity ratings reflected high satisfaction with the digital format, highlighting its feasibility and practicality for classroom use. Compared to paper-based contracts, the digital format offers automated timing, real-time visual and auditory feedback, and self-monitoring cues, suggesting mechanisms of change beyond simple digitization. Although findings support the potential effectiveness of digital behavior contracts, conclusions are limited by the small sample size and controlled setting. Future research should compare digital and traditional formats and examine long-term outcomes in naturalistic environments.